"Here Nobody Holds Your Heart": Metaphoric and Embodied Emotions of Birth and Displacement among Karen Women in Australia. (5th March 2014) - Niner, Sara; Kokanovic, Renata; Cuthbert, Denise; Cho, Violet
<x xml:space="preserve">Abstract</x> Our objective was to explore the ways in which displaced Karen mothers expressed emotions in narrative accounts of motherhood and displacement. We contextualized and analyzed interview data from an ethnographic study of birth and emotions among 15 displaced Karen mothers in Australia. We found that women shared a common symbolic language to describe emotions centered on the heart, which was also associated with heart "problems." This, along with hypertension, collapsing, or a feeling of surrender were associated responses to extremely adverse events experienced as displaced peoples. A metaphoric schema of emotional terms centered on the heart was connected to embodied expressions of emotion related to illness of the heart. This and other embodied responses were reactions to overwhelming difficulties and fear women endured due to their exposure to political conflict and global inequity.